Energy Storage and Conversion Systems - Kuperman, Alon; Lampasi, Alessandro (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Energy storage and conversion are crucial research and industry topics, especially within the context of sustainable development. Scientific and technological progress in these fields have the potential to improve energy use efficiency across traditional, renewable and unconventional sources. Energy storage technologies, including batteries, fuel cells, supercapacitors (ultracapacitors) and superconducting magnetic energy storage (SMES), combined with decreasing costs, are creating new scenarios and opportunities in the development and market of energy generation, grids, industrial plants, complex systems and consumer electronics. This reprint collected some of the latest developments and applications in these interdisciplinary fields, offering a common framework for authors from different research areas.